Biocementation for clay - Thiri Htun Wai (Nanyang Technological University, 2020)
In this research, the effect of biocementation on the unconfined compressive strength of clay has been studied. Biocementaion is the use of microbially induced calcium precipitate (MICP) to improve the strength of clay. In this research, kaolin was mixed with different proportions of bacterial solution (Bacillus sp), calcium carbide residue and urea. The volume of bacterial solution was fixed at 30% of the total mass of clay and carbide. Calcium carbide residue was used as the source of calcium ion for calcite precipitate. The samples were then left to be cured for 7, 14 and 28 days. The properties of MICP treated soil were assessed by the unconfined compressive (UC) test, recording unconfined compressive strength at 7,14 and 28 days, followed by water content. The results show that the compressive strength recorded after 14 and 28 curing days are approximately similar. The results indicate an increased in strength of more than 50% after 28 curing days. The maximum strength of an untreated sample is 310 kPa while the maximum strength of the biocemented sample is found to be 470 kPa. The findings also show that there is an inverse relation between the water content of samples and the unconfined compressive strength.